Rethinking Property Rights Over Water-Based Constructions: Comparative Insight from Indonesia and Selected Jurisdiction - Oemar Moechthar; Agus Sekarmadji; Gading Ariyo Caesar Putra Prayogi; Mochammad Thanthowy Syamsuddin (Faculty of Law Universitas Jenderal Soedirman, 2026)
Property rights over water-based constructions present a complex legal issue within Indonesia’s agrarian law system. Existing regulations, including the Agrarian Law of 1960 and Government Regulation No. 18 of 2021 on Management Rights, Land Rights, and Land Registration, do not explicitly regulate the legal status of structures built above water surfaces. This regulatory gap creates uncertainty regarding ownership. The spatial control and the classification of such constructions within the existing land law framework are needed to examine. This study examines the legal framework governing water-based constructions in Indonesia through a qualitative doctrinal approach combined with comparative legal analysis. It evaluates relevant statutory provisions, legal concepts of land and spatial rights, and selected international practices to identify regulatory gaps and potential solutions. The comparative analysis draws on experiences from jurisdictions that have addressed similar issues, particularly in relation to the classification of floating structures and the separation between land rights and building rights. The findings indicate that the current Indonesian framework lacks conceptual clarity in addressing constructions situated above water, resulting in overlapping institutional authority and inconsistent regulatory practices. A key insight from the comparative analysis is the potential relevance of the horizontal separation principle (applied in jurisdictions such as Japan), which distinguishes between land ownership and building rights. This approach may provide an alternative model for regulating water-based constructions in Indonesia. This study concludes that clearer regulatory integration and inter-agency coordination are essential to ensure legal certainty, effective spatial governance, and sustainable development in water-based environments.